(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Essential oils are being researched as antimicrobial agents to fight infectious disorders due to antibiotic resistance. This work loads dill essential oil, Anethi aetheroleum, into solid lipid nanoparticles (SLNs) and tests their antibacterial efficacy. Effectively administering essential oils using SLNs increases bioavailability and stability. A modified solvent emulsification-evaporation approach created Anethi aetheroleum-containing SLNs. They were then tested for physicochemical qualities and antibacterial activity against many harmful pathogens. Enveloping the Anethi aetheroleum in SLNs created stable nanostructures with the right shape and particle size. Anethi aetheroleum-loaded SLNs were highly effective against bacteria in antibacterial testing. Given these findings, SLNs should be carefully examined as a way to distribute essential oils, particularly Anethi aetheroleum, to fight bacterial infections and reduce antibiotic resistance.